Students’ perceptions of learning mathematics at pre- diploma level/ Norfazillah Matmali, Nur Aliyah Jazuli and Nasrah Naharu - Matmali, Norfazillah; Jazuli, Nur Aliyah; Naharu, Nasrah (Universiti Teknologi MARA, Sabah, 2024)
Pre-diploma students' performance in mathematics is a significant concern, impacting their academic progression and future career options. This study aims to identify key factors influencing the mathematical performance of pre-diploma students. Employing a quantitative descriptive survey design, this research examined the role of various factors, including student characteristics, instructional strategies, and institutional support. The findings revealed that lecturer influence, interest, and attitude significantly impact student performance. These results suggest that improving mathematics education at the pre-diploma level requires a holistic approach, considering not only student factors but also instructional strategies and institutional support. The implications of this study are discussed in relation to enhancing the teaching and learning of mathematics at the pre-diploma level.